Environment, Development and Change in Rural Asia-Pacific: Between local and global - Connell, John; Waddell, Eric (Routledge Pacific Rim Geographies, 2006)
This volume examines the economic, political, social and environmental challenges facing rural communities in the Asia-Pacific region, as global issues intersect with local contexts. Such challenges, from climatic change and volcanic eruption to population growth and violent civil unrest, have stimulated local resilience amongst communities and led to evolving regional institutions and environment management practices, changing social relationships and producing new forms of stratification. Bringing together case studies from across mainland Southeast Asia and the Island Pacific, an expert team of international contributors reveal how communities at the periphery take charge of their lives, champion the virtues of their own local systems of production and consumption, and engage in the complexities of new structures of development that demand a response to the vacillations of global politics, economy and society. Inherent in this is the recognition that 'development' as we have come to know it is far from over. Each chapter emphasizes the growing recognition that ecological and environmental issues are key to any understanding and analysis of structures of sustainable development. Providing diverse multidisciplinary theoretical and empirical perspectives, Environment, Development and Change in Rural Asia-Pacific makes an important contribution to the revitalization of development studies and as such will be essential reading for scholars in the field, as well as those with an interest in Asia-Pacific studies, economic geography and political economy.